The Impact of the Covid-19 Pandemic on Indonesia's Monetary Stability - Junaedi, Dedi; Norman, Efrita; Romli, Moh; Salistia, Faisal (International Conference on Islamic Studies, 2020)
This study aims: (1) to analyze the effects of the pandemic and the differences in policies in handling the Covid-19 pandemic on Indonesia's monetary stability; (2) to analyze the effect of money supply, BI-rate, market operations, stock index on Indonesia's monetary stability. This study uses quantitative analysis methods with multiple dummy variable regression. As a result, the number of pandemic cases and differences in policies had a significant effect on the stability of the rupiah. Simultaneously, the stability of the rupiah exchange rate is influenced by pandemic variables (cases, deaths, recovery and pandemic management policies, money supply (M1, M2), market operations (conventional and sharia), reference interest rates (BI-rate), inflation rate. foreign exchange reserves, financial stock index. These independent variables are correlated with the rupiah exchange rate with a correlation coefficient of R2 0.927073. The pandemic management policy, whatever its name, tends to weaken the rupiah exchange rate position. the exchange rate of the rupiah, meanwhile the formation of a task force had a lighter impact on pressing the rupiah compared to other policies.